Prediction of tangential cutting force in end milling of medium carbon steel by coupling design of experiment and response surface methodology - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry (The Institution of Engineers (IEB), Bangladesh, 2009)
The present paper discusses the development of the first and second order models for predicting the tangential cutting force produced in end-milling operation of medium carbon steel. The mathematical model for the cutting force prediction has been developed, in terms of cutting parameters cutting speed, feed rate, and axial depth of cut using design of experiments and the response surface methodology (RSM). All the individual cutting parameters affect on cutting forces as well as their interaction are also investigated in this study. The second order equation shows, based on the variance analysis, that the most influential input parameter was the feed rate followed by axial depth of cut and, finally, by the cutting speed. Central composite design was employed in developing the cutting force models in relation to primary cutting parameters. The experimental results indicate that the proposed mathematical models suggested could adequately describe the performance indicators within the limits of the factors that are being investigated. The adequacy of the predictive model was verified using ANOVA at 95% confidence level. This paper presents an approach to predict cutting force model in end milling of medium carbon steel using coated TiN insert under dry conditions and full immersion cutting.